KNOWLEDGE OF PRINCIPALS AND THEIR ATTITUDE TOWARDS THE IMPLEMENTATION OF INCLUSIVE EDUCATION AS DEFINED IN THE SECTOR POLICY FOR LEARNERS AND TRAINEES WITH DISABILITIES IN KISUMU COUNTY, KENYA - Ogenga, Maureen (Nazarbayev University Graduate School of Education, 2022)
School principals’ roles are paramount and their presence is vital during creation of school cultures. Their knowledge about inclusive education is therefore necessary to ensure success during the implementation process. This study aims to explore the knowledge of school principals and their attitude towards the implementation process. Described as exploratory research, this study adopted a qualitative approach, where semi-structured interviews were conducted on six secondary school principals about their knowledge of IE, challenges encountered during implementation if any and mitigations for the challenges. The data was thematically analyzed. The sector policy document was also analyzed in connection to its objectives and themes. The findings illustrated that most principals have a positive attitude towards implementation of inclusive education even though most of them lack adequate knowledge and skills to handle learners with special educational needs and implement inclusive education. The challenges experienced contributed to the negative attitude by some principals. Mitigations of most of the challenges were already outlined in form of strategies in the sector policy document. Therefore, what is required is training, constant communication and follow-up from the government through the Ministry of Education. Keywords: Inclusive education, special educational needs, principals, policy analysis, sector policy.
Keywords: inclusive education; special educational needs; principals; policy analysis; sector policy; Research Subject Categories::SOCIAL SCIENCES; Type of access: Open Access